Exophytic colonic carcinoma complicated by gastrocolic fistula mimicking a giant gastric mass: a case report and brief review - Deng, Xiaofeng; Zhang, Zequn (Frontiers in Oncology, 2025)
Colon cancer rarely presents as a giant exophytic mass that mimics a primary gastric malignancy. Such misleading features can result in diagnostic pitfalls and inappropriate surgical planning. We herein report a unique case of colonic adenocarcinoma involving the gastric wall and forming a gastrocolic fistula, initially misdiagnosed as gastric cancer. Moreover, we conducted a brief literature review on the diagnostic challenges associated with exophytic colonic carcinomas to enhance the understanding and management of this rare entity. A 60-year-old man presented with a one-month history of melena and fatigue. Initial abdominal CT and gastroscopy at a local hospital revealed a large exophytic mass occupying the gastric body, leading to a provisional diagnosis of gastric cancer. Biopsy suggested high-grade intraepithelial neoplasia with focal carcinoma. At our center, further evaluation including colonoscopy and PET/CT revealed a mass at the splenic flexure of the colon infiltrating the stomach wall. A multidisciplinary team discussion raised suspicion for colonic origin. The patient underwent en bloc resection including extended left hemicolectomy, partial gastrectomy, lymphadenectomy, distal pancreatectomy, splenectomy and postoperative HIPEC. Surgical findings confirmed a gastrocolic fistula. Final pathology revealed moderately-poorly differentiated adenocarcinoma of colonic origin invading the gastric wall. The patient recovered well postoperatively and completed six cycles of adjuvant chemotherapy, remaining recurrence-free at the 12-month follow-up. This case highlights a rare presentation of splenic flexure colon cancer mimicking a gastric tumor, underlining the importance of thorough preoperative evaluation, multidisciplinary discussion, and awareness of diagnostic traps in trans-organ gastrointestinal oncology.